The Implications of Legal Uncertainty of the Provisions on Hybrid Threats in the Indonesia National Defense System - Muhammad Hamdi Karim; Mhd. Halkis; Susaningtyas Nefo Kertopati (West Science Law and Human Rights, 2023)
The inclusion of hybrid threats in Law No. 23/2019 concerning Management of National Resources for National Defense can be considered an early preparation made within the national defense system to confront increasingly complex and multidimensional threats. However, it is important to question whether the addition of a new type of threat, namely hybrid threats, in Law No. 23/2019 on Management of National Resources for National Defense, which was not previously regulated in Law No. 3/2002 concerning National Defense, is in line with the principle of legal certainty. This legal research aims to analyze the legal certainty of the provisions regarding hybrid threats in Law No. 23/2019 concerning Management of National Resources for National Defense and its implications on policies related to state emergencies and the mobilization of reserve components. The study adopts a normative legal research method. The literature review collects information from document analysis, which is qualitatively analyzed. The data analysis is descriptive-analytical in nature. The results of the study show that the provisions regarding hybrid threats in Law No. 23/2019 concerning Management of National Resources for National Defense create legal uncertainty due to the disharmony in the legislative regulations. There is a need to fill the legal gap in addressing complex and multidimensional threats through the formulation of hybrid threats. However, this has led to a situation of legal uncertainty regarding the regulation of mobilizing reserve components, which should only be mobilized to face military threats when the President declares a state of military emergency or a state of war.